Psychosocial Analysis of Aging in the Elderly: Its Social Representations - Castro, Jefferson Luiz de Cerqueira (2020)
Objective. This study aimed to identify and compare the social representations of aging built by seniorparticipants of cohabiting groups for the elderly (G1) and non-participant elderly (G2). Method. The participation of 60 elders was equally distributed by gender. A socio-demographic questionnaire, the Free Word Association Technique (FAWT), and a semi-structured interview were all applied. The data collected by the FAWT were analyzed by the technique of semantic networks, while the interviews were investigated by IRaMuTeQ software. Results. Overall, it was found that the elderly in cohabitation groups characterized aging with positive aspects, associating it with health and physical activities while those who did not participate associated it with negative aspects related to disease, loss and decline.